Where is my parcel? A review of crowd logistics revolution in Malaysia - Nor Rokiah Hanum, Md Haron; Lee, Khai Loon; Nawanir, Gusman (Akademia Baru, 2023)
This research aims to explore the crowd logistics concept and discover crowd logistics evolution in the Malaysia logistics industry. Employs a systematic literature review approach by using PICo or mnemonic, which signifies ‘P’ (Population or Problem), ‘I’ (Intervention or Exposure) and ‘Co’ (Context). This paper evaluates the evolution of crowd logistics in Malaysia starting with conventional logistics, the introduction of raid hailing, last-mile delivery, crowd logistic and the future of crowd intelligence. The history of crowd logistics expansion has become prominent with the integration of technology and existing infrastructure which allows greater flexibility, customization and efficiency in logistics and transportation delivery. Addressing the crowd logistics revolution has shaped the development of future crowd logistics to be available in the supply chain and maximize the value creation in the Malaysia logistics industry.